Kajian Kelimpahan Mikroplastik di Perairan Teluk Benoa Provinsi Bali - Nugroho, Dimas Hafidh; Restu, I Wayan; Ernawati, Ni Made (Current Trends in Aquatic Science; Vol 1 No 1 (2018)DO - 10.24843/CTAS.2018.v01.i01.p11, 2018)
Benoa Bay is one of the water areas with a fairly complex activity, ranging from benoa port activities, watersports tours, as well as activities from residential areas. The activity is thought to contribute to the pollution of marine debris on the bay of Benoa. The purpose of this study is to determine the type and abundance of microplastic contained in the waters of Benoa Bay, Bali. This study was conducted from March to May 2018. Microplastic sampling in water using 200 µm plankton net which was withdrawn for 10 minutes. Method microplastic sampling in sediments using a shovel. The results showed that there are 3 types of microplastic found in water and sediment of Benoa Bay waters are fragment, film, and fiber. The highest microplastic type in the waters comes from the type of fragment with an abundance of 0.26 particles / m³ found at station 3. The highest total microplastic abundance in the waters is present at station 3 with an abundance of 0.58 particles / m³. The highest microplastic type in the sediment comes from the type of fragment with an abundance of 57 particles / kg found at station 1. The highest total microplastic in the sediment abundance is present at station 1 with an abundance of 114 particles / kg.